The Sapphires [videorecording (DVD)] - O'Dowd, Chris, 1980-; Mauboy, Jessica. 1989-; Tapsell, Miranda; Kittles, Tory; Mailman, Deborah (Anchor Bay Entertainment, 2013)
Inspired by a true story, it's 1968, and four young, talented Australian Aboriginal girls learn about love, friendship and war when their all girl group The Sapphires entertain the US troops in Vietnam.